Perhitungan Margin Dalam Penyelesaian Pembiayaan Murabahah Sebelum Jatuh Tempo Pelunasan - Premi Anggraini; Agung Hari Wibowo (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2022)
One of the most important teachings is the field of muamalah (Islamic economics). Muamalah occupies an important position in Islam. The purpose of this study is to analyze the calculation of the margin in the settlement of murabahah financing before the maturity of repayment. The research method used is a field study. The results of the study show that the policy of Maybank Sukabumi Branch does not conflict with DSN Fatwa No. 23/DSN-MUI/III/2002 concerning Repayment Deductions in Murabaha. DSN provides a stipulation that if a customer in a murabahah transaction makes a payment on time or earlier than the agreed time, LKS may give a deduction from the payment obligation on the condition that it is not agreed upon in the contract. The amount of the discount as referred to above is left to LKS policies and considerations.